Toad venom poisoning: a case report in Chiang Mai - Sruamsiri, Kamphee (Biomedical Sciences and Clinical Medicine, 2024)
Poisoning after consumption of toad has been reported in many countries. The author reported the case of a Thai man who ingested a cooked toad and developed signs and symptoms consistent with acute digitalis toxicity. The patient presented with gastrointestinal symptoms and alternating bradyarrhythmias, and was treated initially with atropine and dopamine intravenously. He was then admitted to the coronary care unit and placed on a temporary pacemaker. Digoxin specific Fab was given as suggested by the Siriraj Poison Control Center. The patient subsequently improved and was discharged after 6 days of admission.